A COMPARATIVE FATTY ACID COMPOSITIONAL ANALYSIS OF DIFFERENT WILD SPECIES OF MUSHROOMS FROM TURKEY - Zengin, Gokhan; Sarikurkcu, Cengiz; Aktumsek, Abdurrahman; Uysal, sengul; Ceylan, Ramazan; Anwar, Farooq; Solak, Mehmet Halil (Emirates Journal of Food and Agriculture, 2015)
Mushrooms have been recognized as important food items due to their high nutritional and medicinal value. The present work quantifies and compares the fatty acids composition among eleven mushroom species (Auricularia auricular-judae, Collybia dryophila, Flammulina velutipes, Helvella lacunose, Polyporus squamosus, Rhizopogon roseolus, Russula albonigra, Russula delica, Sparassis crispa, Suillus collinitus and Volvariella gloiocephala) harvested from Turkey. The lipid contents of the mushrooms varied from 0.13% (Auricularia auricula-judae) to 2.90% (Sparassis crispa). A total of 14 fatty acids were identified and quantified by gas chromatography in the selected mushrooms species with linoleic (13.17 to 79.41%), oleic (0.71 to 55.07%) and palmitic (8.95 to 30.84%) acids as the major components in the tested mushrooms species. The amount of total saturated fatty acids (SFAs), total monounsaturated FAs (MUFAs) and total polyunsaturated FAs (PUFAs) ranged from 13.97 to 59.44%, 0.94 to 55.44% and 13.54 to 79.93%, respectively. Moreover, the mushrooms tested can be explored as a rich dietary source of essential fatty acids (13.34-79.76%) for human nutrition.